Accounting Perspective of Malang Bantengan Culture with an Ethnomethodological Approach - Utami, Riski Nur; Sopanah, Ana; Bahri, Syamsul (Magister Akuntansi Universitas Pancasila, 2025)
Purpose: This research aims to uncover the values of local wisdom contained in